Kinematics and Robot Design II (KaRD2019) and III (KaRD2020) - Di Gregorio, Raffaele (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This volume collects papers published in two Special Issues "Kinematics and Robot Design II, KaRD2019" (https://www.mdpi.com/journal/robotics/special_issues/KRD2019) and "Kinematics and Robot Design III, KaRD2020" (https://www.mdpi.com/journal/robotics/special_issues/KaRD2020), which are the second and third issues of the KaRD Special Issue series hosted by the open access journal robotics.The KaRD series is an open environment where researchers present their works and discuss all topics focused on the many aspects that involve kinematics in the design of robotic/automatic systems. It aims at being an established reference for researchers in the field as other serial international conferences/publications are. Even though the KaRD series publishes one Special Issue per year, all the received papers are peer-reviewed as soon as they are submitted and, if accepted, they are immediately published in MDPI Robotics. Kinematics is so intimately related to the design of robotic/automatic systems that the admitted topics of the KaRD series practically cover all the subjects normally present in well-established international conferences on "mechanisms and robotics".KaRD2019 together with KaRD2020 received 22 papers and, after the peer-review process, accepted only 17 papers. The accepted papers cover problems related to theoretical/computational kinematics, to biomedical engineering and to other design/applicative aspects.